2023
DOI: 10.1186/s12958-023-01102-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-sensitive activation of SGK1 induces M2 macrophages with anti-inflammatory properties and a Th2 response at the maternal–fetal interface

Abstract: Background Decidual macrophages participate in immune regulation at the maternal–fetal interface. Abnormal M1/M2 polarization of decidual macrophages might predispose immune maladaptation in recurrent pregnancy loss (RPL). However, the mechanism of decidual macrophage polarization is unclear. We explored the role of Estradiol (E2)-sensitive serum-glucocorticoid regulated kinase (SGK) 1 in promoting macrophage polarization and suppressing inflammation at the maternal–fetal interface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Some research found that LPS can exert an impact on the differentiation of monocytes to macrophages. Th1 cytokine, like LPS and IFN-ϒ induces monocyte differentiation to M1 macrophage [ 34 , 41 , 42 ]; Th2 cytokine, like IL-10, IL-4, IL-13 can induce monocyte differentiation to M2 macrophage [ 8 , 22 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some research found that LPS can exert an impact on the differentiation of monocytes to macrophages. Th1 cytokine, like LPS and IFN-ϒ induces monocyte differentiation to M1 macrophage [ 34 , 41 , 42 ]; Th2 cytokine, like IL-10, IL-4, IL-13 can induce monocyte differentiation to M2 macrophage [ 8 , 22 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many research have found that the balance of M1/M2 macrophage proportion in the uterus significantly impacts early pregnancy [ 18 , 19 ]. M1 macrophages induce pro-inflammatory response and host defense upon uteroplacental infection; M2 macrophages take up to 50% of total macrophages in early to mid-pregnancy uterus and are thought to exert immunosuppressive effect and mediate fetal-maternal immune tolerance [ 5 , 20 22 ]. Successful pregnancy needs to keep a proper percentage of M1 and M2 macrophage in the uterus.…”
Section: Introductionmentioning
confidence: 99%
“…M1 macrophages, characterized by classical activation, exhibit reduced susceptibility to glutamate metabolism [ 32 ]. Upon activation, these macrophages promptly initiate a proinflammatory response to the occurrence of reproductive system-associated events by detecting microbial components, including signaling lipoprotein, and damaged-associated molecular patterns that are released from shed abortive material resulting from sudden symptoms of miscarriage [ 33 ]. Additionally, M1 macrophages are closely linked to organism metabolism [ 34 ], as they rely on aerobic glycolysis to generate ATP, which leads to increased glucose and glutamine consumption while simultaneously inhibiting metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that SGK1 localizes to the acrosome during the course of epididymal maturation, and could be involved in endowing sperm with basal motility by phosphorylating and inactivating of glycogen synthase kinase 3 (GSK3) [ 55 ] and downregulating the abundance of β-catenin protein in the BTB [ 57 ]. Other studies have shown that SGK1 promotes the proliferation and anti-apoptosis of immature SCs [ 58 ] through PI3K, PDK1, AKT signaling pathways [ 59 , 60 ], regulates the protein synthesis and cytoskeleton of mature SCs to change the structure of BTB [ 60 ], and promotes spermatogenesis. In addition, SGK1 highlights the role of FoxO3a in regulating oxidative stress [ 61 ], which can damage BTB by destroying BTB-associated junction proteins and inducing apoptosis of Sertoli cells, leading to testicular damage and spermatogenesis disorders [ 62 ], which could lead to male infertility [ 63 ].…”
Section: Sgk1 Involvement In Gametogenesismentioning
confidence: 99%